2018
DOI: 10.3390/rs10020167
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial CDOM in Lakes of Yamal Peninsula: Connection to Lake and Lake Catchment Properties

Abstract: Abstract:In this study, we analyze interactions in lake and lake catchment systems of a continuous permafrost area. We assessed colored dissolved organic matter (CDOM) absorption at 440 nm (a(440) CDOM ) and absorption slope (S 300-500 ) in lakes using field sampling and optical remote sensing data for an area of 350 km 2 in Central Yamal, Siberia. Applying a CDOM algorithm (ratio of green and red band reflectance) for two high spatial resolution multispectral GeoEye-1 and Worldview-2 satellite images, we were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…As a result, algorithms commonly incorporate a green/red ratio (e.g., [47,[131][132][133]). Remote sensing studies focusing on CDOM range in application from identifying trends in inland water carbon content [134,135] to examining landscape-level drivers of CDOM distributions [50,136]. Work in rivers highlights controls of carbon export in arctic landscapes [137] and relationships governing CDOM variation in river estuaries along with the resulting impact on correlated concentrations of methylmercury [68].…”
Section: Colored Dissolved Organic Mattermentioning
confidence: 99%
“…As a result, algorithms commonly incorporate a green/red ratio (e.g., [47,[131][132][133]). Remote sensing studies focusing on CDOM range in application from identifying trends in inland water carbon content [134,135] to examining landscape-level drivers of CDOM distributions [50,136]. Work in rivers highlights controls of carbon export in arctic landscapes [137] and relationships governing CDOM variation in river estuaries along with the resulting impact on correlated concentrations of methylmercury [68].…”
Section: Colored Dissolved Organic Mattermentioning
confidence: 99%
“…A trend of increasing organic matter concentration within lake waters has been observed as a result of recent formation of thermocirques. 48 The concentration of DOC in water extracted from peat layers of thermocirque exposures can reach 243 mg/L. 49 Based on two years of observations (see section 3.3.3), we found that the decreased rate of crater wall thawing and retreat as well as potential dilution by atmospheric precipitation has led to further DOC decline in GEC-1 lake.…”
Section: Water Source In Gec Lakes and Lake Water Chemistrymentioning
confidence: 88%
“…The concentration of DOC in GEC lakes is controlled by the supply of allochtonous organic matter delivered from surrounding areas, peat layers and scattered organic matter in frozen deposits. A trend of increasing organic matter concentration within lake waters has been observed as a result of recent formation of thermocirques . The concentration of DOC in water extracted from peat layers of thermocirque exposures can reach 243 mg/L…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations